Language acquisition: Hesitations in the question/answer dialogic pair - Chacon, Lourenço [UNESP]; Villega, Cristyane de Camargo Sampaio [UNESP] (FapUNIFESP (SciELO), 2015)
Purpose: (1) To verify the existence (or not) of hesitation marks in the beginning of utterances in children's discourse; and (2) to determine to what extent the presence/absence of these marks could be explained by retrievable facts in the production conditions of their discourses. Methods: Interview situations with four children aged 5-6 years attending Kindergarten level II in a public preschool at the time of the data collection were analyzed. The interviews were recorded on audio and video, inside a soundproof booth, with high fidelity equipment. Afterwards, the recordings were transcribed by six transcribers that were specially trained for this task. Transcription rules that prioritized the analyses of hesitations were used. For the analysis of retrievable facts in the production conditions of children's discourse, the dialogic pair question-answer was adopted. Results: A correlation between presence/absence of hesitation in the beginning of utterances in children and type of question (open/closed) made by the collocutor was observed. When the question was closed ended, the utterances were preferably initiated without hesitation marks, and when the question was open ended, the utterances were preferably initiated with hesitation marks. Conclusion: The presence/absence of hesitation marks in the beginning of utterances in children was found to be dependent on the production conditions of their discourses.
Keywords: Child; Child language; Communication; Language and hearing sciences; Language arts; Language development; Linguistics; Speech